2003
DOI: 10.1051/0004-6361:20030338
|View full text |Cite
|
Sign up to set email alerts
|

Observations of water in comets with Odin

Abstract: Abstract. The Odin satellite, which can observe the 1 10 -1 01 rotational line at 557 GHz of ortho water with a high spectral resolution (80 m s −1 ) and a spatial resolution of 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 9 publications
(9 reference statements)
10
65
0
Order By: Relevance
“…5). Nevertheless, there is a systematic offset by a factor of 2.5 between Combi et al (2011) data and the other measurements (Bockelée-Morvan et al 2004;Fink 2009;Lecacheux et al 2003;Schleicher et al 2003). This was also viewed on the comets Hale-Bopp (Combi et al 2000) and Hyakutake (Combi et al 2005) data.…”
Section: Discussion Of Resultsmentioning
confidence: 64%
“…5). Nevertheless, there is a systematic offset by a factor of 2.5 between Combi et al (2011) data and the other measurements (Bockelée-Morvan et al 2004;Fink 2009;Lecacheux et al 2003;Schleicher et al 2003). This was also viewed on the comets Hale-Bopp (Combi et al 2000) and Hyakutake (Combi et al 2005) data.…”
Section: Discussion Of Resultsmentioning
confidence: 64%
“…Its observation in comets has been a major observing topic for Odin. Previous observations of this line in comets have been reported in Neufeld et al (2000), Lecacheux et al (2003), and Biver et al (2007a).…”
Section: Introductionmentioning
confidence: 62%
“…Several studies of the 1 10 → 1 01 transition observed in other comets suggest a lower electron density (N. Biver, priv. comm., based on data presented by Lecacheux et al (2003), and ). In the absence of mapping observations and multi-line observations of water rotational transitions that can be used to constrain the electron density, the uncertainty in the electron density limits the accuracy of the water production rate that can be derived from submillimeter observations.…”
Section: Radiative Transfer Modelmentioning
confidence: 99%